DESEMPENHO DE BORREGOS CONFINADOS COM DIETA DE ALTO CONCENTRADO SUPLEMENTADOS COM BACILLUS AMYLOLIQUEFACIENS - Sene, Alexsander Ribeiro de (2020)
Recently, there has been a renewed interest in looking for ways to increase performance of confined lambs, to reduce seasonality of production with greater uniformity in the final product. In this sense, studies related to lamb supplementation in confinement with probiotics has been carried out, showing an increase in weight gain and better Convert food. However, no research was found that addressing Bacillus amyloliquefaciens supplementation for lambs in containment. Therefore, the main objective of the study was to investigate the effect of supplementation with Bacillus amyloliquefaciens in lamb feeding confined about performance, hematological, biochemical and health parameters ruminal. For that, 24 female were used, of the Texel x Ile de France races, with age 150-210 days, weaned, weighing 20.56 ± 5 kg, randomly separated in two groups: Control group, received concentrate at 3.5% of live weight; it's the Bacillus Group received concentrate at 3.5% of live weight, inoculated with Bacillus amyloliquefaciens. A used experimental dose of Bacillus amyliquefaciens was 2.0 x 106 cfu/kg of PV. The data indicated that supplementation B. amyloliquefaciens promoted GMD 13% higher, there was no difference for weight and carcass yield between groups. Supplementation with B. amyloliquefaciens was not harmful to the ruminal health of the animals.